2004
DOI: 10.1196/annals.1308.065
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent and Adult Rats' Aversion to Flavors Previously Paired with Nicotine

Abstract: Despite the high prevalence of adolescent smoking, few studies have examined nicotine sensitivity during this developmental period. In the present study we examined adolescent and adult rats' preference/aversion for a flavor previously paired with nicotine. Paired (nicotine + Kool-Aid) and unpaired (Kool-Aid) solutions were presented in the home cage on alternating nights, with water given during the light phase for six days. A choice test was conducted 24 hr after the last night of conditioning, with both fla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
63
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(77 citation statements)
references
References 3 publications
13
63
1
Order By: Relevance
“…The present study further extends the results of the ICSS study because it utilized a paradigm involving environmental associations with the affective properties of nicotine [5]. Second, the present study is consistent with the finding that adult rats display taste aversion for a solution previously paired with nicotine; however, adolescent rats do not display this taste aversion [27]. Lastly, adolescent rats are less sensitive to the anxiety-inducing effects of withdrawal relative to adults [28].…”
Section: Discussionsupporting
confidence: 86%
“…The present study further extends the results of the ICSS study because it utilized a paradigm involving environmental associations with the affective properties of nicotine [5]. Second, the present study is consistent with the finding that adult rats display taste aversion for a solution previously paired with nicotine; however, adolescent rats do not display this taste aversion [27]. Lastly, adolescent rats are less sensitive to the anxiety-inducing effects of withdrawal relative to adults [28].…”
Section: Discussionsupporting
confidence: 86%
“…The results of these studies suggest that nicotine is more rewarding and less aversive in adolescents compared with adults (Vastola et al, 2002;Belluzzi et al, 2004;Torrella et al, 2004;Wilmouth and Spear, 2004;Shram et al, 2006). There are several possible reasons for this potential discrepancy.…”
Section: Nicotine Self-administration In Adolescent and Adult Ratsmentioning
confidence: 93%
“…Adolescent rats share many behavioral and neurobiological characteristics with human adolescents, and have been useful in determining factors contributing to vulnerability to drugs, including nicotine, during this ontogenetic period (Spear, 2000). Using conditioned place preference (CPP) and conditioned taste avoidance (CTA) procedures, we and others reported that adolescent rats are more sensitive to the rewarding effects of nicotine and less sensitive to its aversive effects than adult rats (Vastola et al, 2002;Belluzzi et al, 2004;Torrella et al, 2004;Wilmouth and Spear, 2004;Shram et al, 2006). Furthermore, several investigators reported that adolescent rats may acquire nicotine self-administration faster than adult rats (Levin et al, 2003;Belluzzi et al, 2005;Chen et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Tactile stimulus-elicited vocalization is well documented in cannabinoid-treated rats and is considered an index of a negative drug-induced emotional state (Henriksson and Jarbe, 1971;Giuliani et al, 2000). The reduced aversive effects of cannabinoids in adolescent rats parallel analogous developmental effects observed with alcohol (Philpot et al, 2003) and nicotine (Wilmouth and Spear, 2004). This suggests that certain characteristics of the still-developing adolescent brain may make adolescent rats less sensitive to the use-limiting aversive properties of various drugs of abuse and hence more vulnerable to continued use and addiction.…”
Section: Acute Aversive Effects Of Thcmentioning
confidence: 99%